Maternal experience of domestic violence before and during pregnancy and children's linear growth at 15 years: Findings from MINIMat trial in rural Bangladesh - Shirin Ziaei; Ruchira Tabassum Naved; Syed Moshfiqur Rahman; Anisur Rahman; Eva‐Charlotte Ekström (Wiley, 2021)
Abstract Literature concerning negative impacts of domestic violence (DV) against women on their children's health is growing; however, little is known about the long‐term effect of maternal exposure to DV before and/or during pregnancy on their children's growth. Using data from the MINIMat cohort, we have evaluated the association between maternal lifetime experience of DV, measured in late pregnancy, with their children's linear growth at 15 years (n = 2240) in rural Bangladesh. A modified version of conflict tactic scale was used to record the maternal experience of physical, sexual, emotional DV and controlling behaviour. Children's height was measured by trained nurses during their clinical visits at 15‐year follow‐up. Compared to the women with no experience of DV, children of women with experience of any physical, sexual or emotional DV before and/or during pregnancy had the significantly lower height for age Z‐scores (HAZs) at the age of 15. No significant association between maternal experience of controlling behaviour and their children's linear growth was observed in terms of HAZ. Results from this study suggest that maternal experience of DV before and/or during pregnancy might be associated with impaired long‐term linear growth within their children.